A Pilot Study of a Distress Tolerance Treatment for Opiate-Dependent Patients Initiating Buprenorphine: Rationale, Methodology, and Outcomes. (September 2014) - Brown, Richard A.; Bloom, Erika Litvin; Hecht, Jacki; Moitra, Ethan; Herman, Debra S.; Stein, Michael D.
Buprenorphine, an opioid that is a long-acting partial opiate agonist, is an efficacious treatment for opiate dependence that is growing in popularity. Nevertheless, evidence suggests that many patients will lapse within the first week of treatment and that lapses are often associated with withdrawal-related or emotional distress. Recent research suggests that individuals' reactions to this distress may represent an important treatment target. In the current study, we describe the development and outcomes from a preliminary pilot evaluation ( N = 5) of a novel distress tolerance (DT) treatment for individuals initiating buprenorphine. This treatment incorporates exposure-based and acceptance-based treatment approaches that we have previously applied to the treatment of tobacco dependence. Results from this pilot study establish the feasibility and acceptability of this approach. We are now conducting a randomized controlled trial of this treatment that we hope will yield clinically significant findings and offer clinicians an efficacious behavioral treatment to complement the effects of buprenorphine.